Quantum Learning to Improve the Fourth Graders’ Science Achievement in An Elementary School - Nimas Vindy; Armadyaningtyas; Woro Sri Hastuti (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to increase the science learning achievement. The subjects of this study were 20 students of fourth grade students at Imogiri Elementary School, who used Quantum Learning model. The research design refers to the classroom action research which takes place in two cycles. Data collection through tests, observation and documentation. The data analysis techniques used are qualitative and quantitative descriptive techniques. At the natural syntax of Quantum Learning model, the teacher provides examples of real 3-dimensional models to students and the division into more heterogeneous groups. In the naming activity, the teacher explains the learning material using two languages, namely Indonesian and a foreign language. At the demonstrate syntax the teacher directs students to convey the results of their discussion in turn. The success criteria are if ≥ 75% of the total number of students get a score ≥ 75. This research shows the results of an increase in science learning achievement after using Quantum Learning. In cycle I the average student learning achievement was 73.25 then increased to 83.50 in cycle II. Based on this, it can be concluded that Quantum Learning can improve the science learning achievement of class IV students.